"L’indegnità di parlare per gli altri": Anormalità e confessione nell’opera di Foucault - Giuseppe Vena (Kaiak)
In the mid-1970s, a recurring theme in Michel Foucault’s production was that of abnormals, that is, all those figures such as criminals, internees, and hermaphrodites who are placed on the margins of society. Rather than demonstrating a supposed romanticization of marginality, the 1974/1975 lecture series represents an attempt to see how power functions when it comes into contact with “abnormal” subjects. Through the publication of the memoirs of Pierre Rivière, Herculine Barbin, and the lettres de cachet of the archives, an interest emerges in Foucault that goes beyond the analytics of power: when the dysphoric subject can truly take the floor, mostly through the experience of writing, he represents a truth other than that of power. It is during this period that Foucault begins to reflect on the possibility of linking resistance and speech-taking through a first-person assumption of truth destined later to be revived through the theme of Greek parrésia.